Life Stress, Strain, and Deviance Across Schools: Testing the Contextual Version of General Strain Theory in China - Zhang, Jinwu (International journal of offender therapy and comparative criminology, 2018)
General Strain Theory delineates different types of strain and intervening processes from strain to deviance and crime. In addition to explaining individual strain-crime relationship, a contextualized version of general strain theory, which is called the Macro General Strain Theory, has been used to analyze how aggregate variables influence aggregate and individual deviance and crime. Using a sample of 1,852 students (Level 1) nested in 52 schools (Level 2), the current study tests the Macro General Strain Theory using Chinese data. The results revealed that aggregate life stress and strain have influences on aggregate and individual deviance, and reinforce the individual stress-deviance association. The current study contributes by providing the first Macro General Strain Theory test based on Chinese data and offering empirical evidence for the multilevel intervening processes from strain to deviance. Limitations and future research directions are discussed.